Detachable modified silane sealing adhesive as well as preparation method and application thereof
By using a combination of heavy calcium carbonate, talc and aluminum hydroxide, combined with modified silane polymer and plasticizer, the problem of the inability to disassemble the modified silane sealing material in the prior art is solved, and high Removable modified silane sealing adhesive with strength and low peel strength, suitable for home improvement and construction and handmade DIY applications.
Patent Information
- Application Number
- CN202411488882.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-10
AI Technical Summary
Existing modified silane sealing materials cannot be detachable from home decoration substrates at room temperature, and often require auxiliary agents or high temperature conditions.
Using a combination of heavy calcium carbonate, talc and aluminum hydroxide, the high-strength removable removable can be prepared without additive disassembly at room temperature through the coordinated action of different particle sizes, combined with modified silane polymers and plasticizers. Type modified silane sealing adhesive.
It realizes freehand disassembly under normal temperature without additives, with peel strength close to 0N/mm, and excellent product durability and bonding effect, making it suitable for reuse.
Smart Images

Figure CN119286451A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealing adhesives, and in particular, relates to a detachable modified silane sealing adhesive and a preparation method and application thereof. Background Art
[0002] In home decoration and DIY, various metal plates, tiles, glass and other substrates are often used, and silane-modified sealants have excellent adhesion to these substrates. In order to meet the new ideas and new decoration methods that users constantly produce during use, the already bonded substrates need to be removable in a non-destructive manner.
[0003] In the current existing technology, some systems of adhesives are partially removable by adding expandable fillers at high temperatures or by treating with additives such as debonding agents, but ordinary modified silane sealing materials still cannot achieve the removability of various home decoration substrates.
[0004] Therefore, there is an urgent need to find a new type of removable modified silane sealing adhesive. Only a simple preparation method is required to compound the components in strict proportions. It can be well bonded to various common home improvement substrates and can quickly form a high-strength removable modified silane sealing adhesive. At the same time, it can be disassembled at room temperature without the aid of any additives, and it is environmentally friendly and non-toxic. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a detachable modified silane sealing adhesive and a preparation method and application thereof. Only a simple preparation method is used and the components are compounded in strict proportions, so that good adhesion to various common home improvement substrates can be achieved, and a high-strength detachable modified silane sealing adhesive can be quickly formed. At the same time, under the premise of ensuring a good bonding effect, the detachable modified silane sealing adhesive can be disassembled by hand at room temperature without the aid of any additives, and is environmentally friendly and non-toxic.
[0006] In order to achieve the above object, the present invention adopts the following scheme:
[0007] On the one hand, the present invention provides a removable modified silane sealing adhesive, comprising a filler, a modified silane polymer and a plasticizer, wherein the filler comprises aluminum hydroxide, and the filler further comprises heavy calcium carbonate and / or talcum powder.
[0008] Furthermore, the filler includes a combination of heavy calcium carbonate, talc and aluminum hydroxide.
[0009] The most critical factor that determines the "removable" performance of the removable modified silane sealing adhesive is the filler. However, in the prior art, some systems of adhesives can only be partially removable by adding expandable fillers at high temperatures or under the treatment of additives such as degumming agents. At room temperature or without the use of other additives, ordinary modified silane sealing materials are still difficult to achieve the removability of various home improvement substrates. Therefore, after a lot of research, the present invention selects different filler combinations for precise compounding, and the prepared removable modified silane sealing adhesive achieves "removability" while ensuring good bonding effect. Not only can it be disassembled by hand at room temperature without the aid of any other additives, solvents, degumming agents, etc., and the peel strength is close to 0N / mm, but also after being coated on the surface of the substrate and stored for more than one year, it will not age or become difficult to peel.
[0010] This effect is achieved, on the one hand, because of the coordination of different particle sizes, that is, the clever combination of filler particle sizes. Fillers with smaller particle sizes can fill the gaps of fillers with larger particle sizes to form a tight and uniform filling structure. This coordination affects the physical properties of the adhesive. Small particle size fillers increase the contact area and filling density, enhance cohesion, and large particle size fillers build a skeleton structure to improve overall stability. When fillers of different particle sizes work together, the adhesive has a more reasonable structure after curing, reducing stress concentration points. When disassembling, the uniform and reasonable structure does not produce strong bonding force, achieving low peel strength and achieving detachability; on the other hand, the coordination of different fillers produces different filling effects, which is based on the chemical and physical properties of the fillers. Different fillers have different surface energy, polarity, hardness, etc. When multiple fillers are combined, the interaction changes the crosslinking density, molecular chain mobility and interface compatibility of the adhesive. For example, some fillers physically or chemically adsorb with the molecular chains of the adhesive, restricting the movement of the molecular chains and increasing the modulus; other fillers introduce rigid structures and reduce toughness. This synergistic effect adjusts the microstructure and mechanical properties of the adhesive, ensuring a certain bonding strength while reducing the peel strength. When disassembly is required, the adhesive does not stubbornly adhere to the surface of the substrate, making it removable and free of aging and difficulty in peeling during long-term storage.
[0011] In some embodiments, the best combination of fillers is screened, and different fillers have different particle sizes. When the filler particle size is too small, "detachability" cannot be achieved; and when the filler particle size is too large, the bonding performance is significantly reduced, and the use requirements of the present invention cannot be met. Therefore, only when the filler is selected as a combination of "heavy calcium carbonate, talcum powder and aluminum hydroxide", and the ratio between the three must be accurately controlled, can a detachable modified silane sealing adhesive with better bonding effect and peeling strength be finally prepared to meet the use requirements of the present invention.
[0012] Furthermore, in terms of mass ratio, the mass ratio of heavy calcium carbonate, talcum powder and aluminum hydroxide in the filler is (1-7.2): (1-7.2): (47.6-55); wherein the particle size of heavy calcium carbonate is 1 μm-10 μm, the particle size of talcum powder is 10 μm-30 μm, and the particle size of aluminum hydroxide is 0.5 μm-5 μm.
[0013] Furthermore, in terms of mass ratio, the mass ratio of heavy calcium carbonate, talcum powder and aluminum hydroxide in the filler is (1-5): (1-5): (50-55)
[0014] Furthermore, in terms of mass ratio, the mass ratio of heavy calcium carbonate, talcum powder and aluminum hydroxide in the filler is (4-5): (4-5): (50-51).
[0015] In some embodiments, in terms of mass ratio, within the range of (1-7.2): (1-7.2): (47.6-55) of the mass ratio of heavy calcium carbonate, talcum powder, and aluminum hydroxide, the addition amount of the three was screened, and the preferred mass ratio was (1-5): (1-5): (50-55). It was found that within the preferred mass ratio range of (1-5): (1-5): (50-55), the ideal bonding effect and the effects of lower peel strength and the like can be achieved; and when the mass ratio of heavy calcium carbonate, talcum powder, and aluminum hydroxide is preferably (4-5): (4-5): (50-51), it has the best high bonding strength and low peel strength at the same time. Based on the influence of fillers of different mass ratios on the performance of the preparation of detachable modified silane sealing adhesive, within a specific mass ratio range, the required high bonding strength and low peel strength can be met while ensuring the durability of the product. Therefore, the preferred filler combination is in a mass ratio of (4-5):(4-5):(50-51).
[0016] At the same time, the particle size of the filler was compared and screened, and it was found that when the particle size of heavy calcium carbonate was 1μm-10μm, the particle size of talc was 10μm-30μm, and the particle size of aluminum hydroxide was 0.5μm-5μm, the bonding effect of the prepared removable modified silane sealing adhesive can be effectively improved, and the peel strength can be significantly reduced while ensuring the bonding effect. When the particle size of the fillers of different components exceeds the above range, if the particle size of heavy calcium carbonate is too small, it may not provide sufficient skeleton structure support, affecting the overall stability; if the particle size is too large, it may cause the synergy with other fillers to deteriorate, and the gaps cannot be effectively filled, reducing the bonding effect. If the particle size of talc is too small, it may not be able to form a good synergistic filling effect with other fillers. If the particle size is too large, it may affect the microstructure and mechanical properties of the adhesive, resulting in an increase in peel strength. If the particle size of aluminum hydroxide is too small, it may not be able to fully exert its chemical and physical properties on the performance of the adhesive. If the particle size is too large, it may be unevenly distributed in the adhesive, affecting the bonding effect and stability. Therefore, the preferred particle size range of the present invention is 1 μm-10 μm heavy calcium carbonate, 10 μm-30 μm talcum powder, and 0.5 μm-5 μm aluminum hydroxide, wherein the talcum powder is talcum powder 2 that meets the particle size requirements, specifically: 5 μm heavy calcium carbonate, 15 μm talcum powder 2, and 1.5 μm aluminum hydroxide.
[0017] Furthermore, the modified silane polymer includes a combination of one or more of SAX750 and SAX400; the plasticizer includes a combination of one or more of phthalate plasticizers, polyether diol plasticizers, and polyether diol plasticizers, the molecular weight of the polyether diol plasticizer is 1000-3000, and the molecular weight of the polyether diol plasticizer is 3000-5000; the modified silane sealing adhesive is a detachable modified silane sealing adhesive.
[0018] In some embodiments, selecting a modified silane polymer having more reaction polymerization centers and a more complex branched structure can significantly reduce the toughness of the sealant composition and improve its shear strength, which is more conducive to achieving "detachability" while meeting the required shear strength; the plasticizer has good water vapor permeability while providing a certain plasticity, and excessive water vapor will destroy the chemical bonding and physical adsorption of the bonding surface, which is conducive to achieving detachability.
[0019] At the same time, the ratio between the two must be precisely controlled. Only when the two are compounded in the optimal ratio can a detachable modified silane sealing adhesive with better bonding effect and peel strength and other properties be obtained to meet the use requirements of the present invention.
[0020] Furthermore, the modified silane polymer includes SAX750, and the plasticizer includes DINP.
[0021] Furthermore, based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive includes 40-60% filler, 15-25% modified silane polymer, and 10-20% plasticizer.
[0022] In some embodiments, for the filling mass ratio of fillers in modified silane sealing adhesives, experiments were conducted to investigate the effects of different filling mass ratios on the performance of removable modified silane sealing adhesives, and it was found that the best bonding effect and product durability can only be achieved when the filling mass ratio of fillers is within the range of 40-60%. When the filler filling mass ratio is lower than 40%, it may not provide sufficient filling and reinforcement, resulting in insufficient bonding strength and affecting the overall performance of the sealing adhesive; when the filler filling mass ratio is higher than 60%, it may cause the toughness of the adhesive to decrease and the hardness to increase, which is not conducive to achieving the "removable" performance requirements, and may also affect the synergy between other components and reduce the overall performance. Therefore, in the present invention, it is preferred that the modified silane sealing adhesive includes 40-60% filler.
[0023] Regarding the filling mass ratio of the modified silane polymer in the modified silane sealing adhesive, it was found that the best bonding effect and shear strength can only be achieved when the filling mass ratio of the modified silane polymer is in the range of 15-25%. When the filling mass ratio of the modified silane polymer is lower than 15%, it may not provide enough bonding active sites, resulting in insufficient bonding strength and failure to meet the use requirements; when the filling mass ratio of the modified silane polymer is higher than 25%, it may cause the toughness of the adhesive to increase and the shear strength to decrease, which is not conducive to achieving the "detachable" performance requirements, and may also affect the synergy between other components and reduce the overall performance. Therefore, in the present invention, it is preferred that the modified silane sealing adhesive includes 15-25% of modified silane polymer.
[0024] Regarding the filling mass ratio of the plasticizer in the modified silane sealing adhesive, it was found that the best plasticity and "removable" effect can only be achieved when the filling mass ratio of the plasticizer is in the range of 10-20%. When the filling mass ratio of the plasticizer is lower than 10%, it may not provide sufficient plasticity, resulting in the adhesive being too hard, which is not conducive to achieving "removability" and may also affect the bonding effect; when the filling mass ratio of the plasticizer is higher than 20%, it may cause excessive water vapor to penetrate, destroying the chemical bonding and physical adsorption of the bonding surface, affecting the bonding effect and product durability. Therefore, in the present invention, it is preferred that the modified silane sealing adhesive includes 10-20% plasticizer.
[0025] Furthermore, based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive includes 45-55% filler, 18-22% modified silane polymer, and 10-15% plasticizer.
[0026] Furthermore, the modified silane sealing adhesive also includes a dewatering agent, a thixotropic agent, an ultraviolet absorber, a light stabilizer, a dye or a pigment, a silane coupling agent, and a catalyst.
[0027] In some embodiments, the addition of a dehydrating agent ensures that the modified silane polymer has good storage properties and avoids moisture reaction therewith during long-term storage; the addition of a thixotropic agent helps to improve the extrusion thixotropic properties of the colloid; the addition of an ultraviolet absorber can prevent ultraviolet rays from damaging the molecular structure of the removable adhesive, maintain the physical properties (such as bonding strength, removable properties, etc.) and chemical stability of the colloid, and extend the service life of the removable modified silane sealing adhesive of the present invention; a light stabilizer helps to stabilize the molecular structure of the removable modified silane sealing adhesive, improve the weather resistance of the colloid, and make the colloid more suitable for external use; dyes or pigments have a coloring effect; silane coupling agents have a bonding promoting effect; and catalysts have a curing accelerating effect.
[0028] Therefore, in the present invention, only by compounding the modified silane polymer and the plasticizer, strictly controlling the dosage ratio, and matching a special filler combination: heavy calcium carbonate + talcum powder + aluminum hydroxide, and strictly controlling the dosage ratio, and controlling the modified silane polymer, plasticizer, filler, thixotropic agent, ultraviolet absorber, light stabilizer, dewatering agent, dye or pigment, silane coupling agent, and catalyst to maintain a special ratio relationship, can the present invention be quickly cured with moisture at room temperature to form an elastomer sealing adhesive, and a detachable modified silane sealing adhesive with better performance in various aspects such as bonding effect, shear strength, hardness, tensile strength, elongation at break, peel strength, stability, etc. is prepared, which can achieve good mechanical properties, stable storage, longer shelf life, can at least hang a 10kg weight, and has good bonding with various common home improvement substrates; at the same time, on the premise of ensuring a good bonding effect, it can also achieve "detachability", which satisfies the requirement that it can be disassembled by hand at room temperature without the aid of any other additives, solvents, degumming agents, etc., and its peel strength is close to 0N / mm.
[0029] Furthermore, based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive also includes 0.5-1.5% dewatering agent, 2.5-5% thixotropic agent, 0.15-0.25% ultraviolet absorber, 0.15-0.25% light stabilizer, 0.5-2% dye or pigment, 0.5-3% silane coupling agent, and 0.3-1% catalyst.
[0030] Furthermore, based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive also includes 0.8-1.2% dewatering agent, 2.5-4% thixotropic agent, 0.15-0.2% ultraviolet absorber, 0.15-0.2% light stabilizer, 0.5-1% dye or pigment, 1-3% silane coupling agent, and 0.4-0.8% catalyst.
[0031] In some ways, in order to obtain better performance, the content of each component in the modified silane sealing adhesive of the present invention was further screened. It was found that, in terms of mass ratio, when the content of each component was within a narrower range, it had a better effect. Specifically, the modified silane sealing adhesive includes 45-55% filler, 18-22% modified silane polymer, 10-15% plasticizer, 0.8-1.2% dewatering agent, 2.5-4% thixotropic agent, 0.15-0.2% ultraviolet absorber, 0.15-0.2% light stabilizer, 0.5-1% dye or pigment, 1-3% silane coupling agent, 0.4-0.8% catalyst. Within the above more precise range, the modified silane sealing adhesive prepared by the present invention can exhibit more outstanding bonding performance, durability and stability, etc., and meet higher requirements for application scenarios.
[0032] Furthermore, the dehydrating agent includes a silane dehydrating agent; the dehydrating agent includes a combination of one or more of vinyltrimethoxysilane, methyltrimethoxysilane, octyltrimethoxysilane, and isobutyltrimethoxysilane.
[0033] Furthermore, the thixotropic agent includes a polyamide wax thixotropic agent; the thixotropic agent includes a combination of one or more of SLX, SLT, and PAMIDD650.
[0034] Furthermore, the ultraviolet absorber includes a benzotriazole ultraviolet absorber; the ultraviolet absorber includes a combination of one or more of Tinuvin 326, Tinuvin 327, and Tinuvin 329.
[0035] The light stabilizer includes a hindered amine light stabilizer; the light stabilizer includes a combination of one or more of Tinuvin 928 and Tinuvin 292.
[0036] Furthermore, the catalyst includes an organic tin compound; the catalyst includes a combination of one or more of the tin catalysts U303, U220H, and U130.
[0037] Furthermore, the dye or pigment includes metal powder; the dye or pigment includes a combination of one or more of titanium dioxide, carbon black, and iron black.
[0038] Furthermore, the silicon coupling agent includes one or more combinations of amino-based silane coupling agents or epoxy-based silane coupling agents.
[0039] Furthermore, the silicon coupling agent includes a combination of one or more of KH792 and KH560.
[0040] Furthermore, the silicon coupling agent includes a combination of KH792 and KH560.
[0041] Furthermore, in the composition of KH792 and KH560, the ratio of the added amounts of KH792 and KH560, calculated by mass ratio, includes (1-2): (1-2).
[0042] Furthermore, in the composition of KH792 and KH560, the ratio of the added amounts of KH792 and KH560 is 2:1 by mass ratio.
[0043] In some embodiments, after adding the silane coupling agent, the bonding performance of the prepared detachable modified silane sealing adhesive can be significantly improved, meeting the use requirements of the present invention, and at the same time, under the premise of ensuring the bonding effect, the peel strength can be significantly reduced, thereby significantly reducing the difficulty of "detachability". This may be because the silane coupling agent promotes the improvement of the bonding ability of the system, so the bonding strength is significantly improved, and the bonding effect is significantly improved, but the synergistic effect between the silane coupling agent and the powder enables the peel strength to be reduced, thereby achieving detachability.
[0044] At the same time, the use of different silane coupling agents also has different effects on the bonding effect, stability and peel strength of the prepared removable modified silane sealing adhesive. The experimental results show that compared with other silane coupling agents, adding a mixture of KH792 and KH560 as a silane coupling agent can effectively improve the bonding effect, stability and tolerable sealing pressure of the prepared removable modified silane sealing adhesive, and at the same time, it can significantly reduce the peel strength while ensuring the bonding effect.
[0045] At the same time, the different addition amounts of KH792 and KH560 result in large differences in the performance of the obtained detachable modified silane sealing adhesive. When any one of the components is increased or decreased, thereby changing the addition ratio of the two components, the performance of the obtained detachable modified silane sealing adhesive will be slightly reduced. Therefore, the preferred addition ratio of KH792 and KH560 in the present invention is (1-2): (1-2); and when the addition ratio of "KH792+KH560" in the silane coupling agent is 2:1, the obtained detachable modified silane sealing adhesive has the best performance, and while ensuring that the plasticity and bonding effects are significantly improved, the peel strength can also reach the minimum, successfully achieving "detachability".
[0046] On the other hand, the present invention provides a method for preparing a detachable modified silane sealing adhesive as described in any one of the above technical solutions, comprising the following steps:
[0047] (1) taking a modified silane polymer, a plasticizer, a filler, a dye or a pigment, and a thixotropic agent, dispersing them, heating them to above 100° C. and dehydrating them for 2-4 hours, and activating the thixotropic agent at the same time;
[0048] (2) Cooling to below 43°C, adding UV absorber and light stabilizer and stirring;
[0049] (3) Add a dehydrating agent, a silane coupling agent, and a catalyst, and stir until the mixture is evenly mixed to obtain a removable modified silane sealing adhesive.
[0050] Furthermore, in step (1), the moisture content must be ensured to be less than 1000 ppm; in step (2), the temperature must be controlled to be less than 43° C. when adding the auxiliary agent.
[0051] The beneficial effects of the present invention are:
[0052] Compared with the prior art, the present invention adopts a special filler combination: heavy calcium carbonate + talcum powder + aluminum hydroxide for precise compounding, and is compounded with a modified silane polymer and a plasticizer, and their dosage ratio is strictly controlled, and at the same time, the modified silane polymer, plasticizer, filler, thixotropic agent, ultraviolet absorber, light stabilizer, dehydrating agent, dye or pigment, silane coupling agent, and catalyst are controlled to maintain a special ratio relationship, so that the present invention can quickly cure with moisture at room temperature to form an elastomer sealing adhesive, and prepare an adhesive with excellent bonding effect, shear strength, hardness, tensile strength, elongation at break. The removable modified silane sealing adhesive has better performance in terms of growth rate, peel strength, stability, etc. It can achieve good mechanical properties, stable storage, longer shelf life, can hang at least 10kg weight, and has good adhesion to various common home improvement substrates; at the same time, under the premise of ensuring good bonding effect, it can also be "removable", which means that it can be disassembled by hand at room temperature without the aid of any other additives, solvents, degumming agents, etc., and its peel strength is close to 0N / mm, which is suitable for sealing and bonding that requires repeated cycles or repair and dismantling, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is the structural formula of SAX400 resin.
[0054] Figure 2 It is the structural formula of SAX750 resin. DETAILED DESCRIPTION
[0055] The present invention will be further described in detail below in conjunction with the examples. It should be pointed out that the examples described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.
[0056] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0057] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0058] The removable modified silane sealing adhesive provided by the present invention, wherein "removable" means: without high temperature or heating conditions, and without the use of other additives such as adhesive removers, it can have the lowest peel strength on the basis of ensuring good bonding and other properties, and can be disassembled by hand. It is known that when the peel strength is greater than 0.5N / mm, it is difficult to achieve removability.
[0059] Example 1 Preparation method of the detachable modified silane sealing adhesive provided by the present invention
[0060] 1. Formula of removable modified silane sealing adhesive
[0061] The present embodiment provides a removable modified silane sealing adhesive, which includes the following components by mass percentage: 15%-25% modified silane polymer, 10%-20% plasticizer, 0.5%-1.5% dewatering agent, 40%-60% filler, 2.5%-5% thixotropic agent, 0.15%-0.25% ultraviolet absorber, 0.15%-0.25% light stabilizer, 0.5%-2% dye or pigment, 0.5%-3% silane coupling agent, 0.3%-1% catalyst. In the present embodiment, specifically 22% modified silane polymer, 10% plasticizer, 1% dewatering agent, 59.6% filler, 3% thixotropic agent, 0.15% ultraviolet absorber, 0.15% light stabilizer, 0.5% dye or pigment, 3% silane coupling agent, 0.6% catalyst.
[0062] Among them, the modified silane polymer is a polyether compound terminated by methoxy groups. In this embodiment, S303H, SAX750 or SAX400 of Japan KANEKA Company are used. The commonly used base resins for MS modified silane sealants are series resins of Japan KANEKA Company, among which SAX750 has more reaction polymerization centers and SAX400 has a more complex branched structure, which is more conducive to reducing the toughness of the sealant composition and improving the shear strength of the sealant composition, and is more conducive to achieving "detachability" while meeting the required shear strength; the S303H structure is similar to SAX400, but the end-capping rates are different. S303H has a low end-capping rate, is easier to infiltrate and bond, is not easy to peel, and has low shear strength. Among them, SAX750 and SAX400 resins with the same formula and proportion have higher hardness, lower elongation at break, and higher shear strength. The structural formulas of SAX400 and SAX750 resins are as follows: Figure 1 and Figure 2 In the structural formula of the SAX400 resin, n is an integer of 2-4, and the molecular weight is 20000-30000; in the structural formula of the SAX750 resin, n is an integer of 2-4, and the molecular weight is 20000-30000. In this embodiment, the modified silane polymer is SAX750 resin.
[0063] The plasticizer includes phthalate esters or polyether diols (molecular weight 1000-3000) compounds or polyether diols (molecular weight 3000-5000) compounds. Phthalate esters can provide good plasticity. Polyether diol compounds can provide certain plasticity and good water vapor permeability. Excessive water vapor will destroy the chemical bonding and physical adsorption of the bonding surface, which is conducive to achieving detachability. Among them, the phthalate ester compounds with the same formula and proportion have a 24-hour curing depth of 2.5-2.8mm, such as DINP (diisononyl phthalate); the polyether diol compounds have a 24-hour curing depth of 3.5-4.2mm, such as INOVOL C220 (polyether diols (molecular weight 1000-3000)) and INOVOL C240 (polyether diols (molecular weight 3000-5000)), specifically: INOVOL C220 is a polyether diol with a molecular weight of 2000, and INOVOL C240 is a polyether diol with a molecular weight of 4000. In this embodiment, the phthalate compound DINP (diisononyl phthalate) produced by Zhejiang Weibo Company is used.
[0064] The dewatering agent includes a silane dewatering agent. The addition of the dewatering agent ensures that the modified silane polymer has good storage properties and avoids the reaction of water with it during long-term storage. The dewatering agent includes vinyl trimethoxy silane, methyl trimethoxy silane, octyl trimethoxy silane, and isobutyl trimethoxy silane. In this embodiment, the dewatering agent is vinyl trimethoxy silane (Hubei Jianghan New Materials Co., Ltd.)
[0065] The fillers include talcum powder, calcium carbonate, aluminum hydroxide, quartz, silicon dioxide, calcium oxide, magnesium oxide, kaolin, etc., and their functions are incremental filling and reinforcing filling. In this embodiment, the filler is a mixture of talcum powder + heavy calcium carbonate + aluminum hydroxide, and the mass ratio thereof is 4.8:4.8:50. At this ratio, it can have the best "removable" effect.
[0066] The thixotropic agent is a polyamide wax thixotropic agent, and the addition of the thixotropic agent helps to improve the extrusion thixotropic properties of the colloid. The thixotropic agent can be SLX, SLT, PAMID D650, etc. In this embodiment, the thixotropic agent is SLT (manufacturer: Arkema, France).
[0067] The ultraviolet absorber includes a benzotriazole ultraviolet absorber. The addition of the ultraviolet absorber can prevent ultraviolet rays from damaging the molecular structure of the removable adhesive, maintain the physical properties (such as bonding strength, removable performance, etc.) and chemical stability of the colloid, and extend the service life of the removable modified silane sealing adhesive of the present invention. The ultraviolet absorber includes a combination of one or more of BASF products: Tinuvin 326, Tinuvin 327, and Tinuvin 329. In this embodiment, the ultraviolet absorber is Tinuvin 326 (manufacturer: Hangzhou Disheng).
[0068] The light stabilizer includes a hindered amine light stabilizer, which helps stabilize the molecular structure of the removable modified silane sealing adhesive, improves the weather resistance of the colloid, and makes the colloid more suitable for external use. The light stabilizer includes a combination of one or more of Tinuvin 928 and Tinuvin 292. In this embodiment, the light stabilizer is Tinuvin 292 (manufacturer: Hangzhou Disheng).
[0069] The dye or pigment includes titanium dioxide, carbon black, iron black and other metal powders, etc., which have a coloring effect. In this embodiment, the dye or filler is specifically titanium dioxide (manufacturer: Shanghai Black Tiger).
[0070] The silane coupling agent includes any one or more combinations of KH792 (Chinese name: N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; manufacturer: Hubei Jianghan) and KH560 (Chinese name: γ-glycidyloxypropyltrimethoxysilane; manufacturer: Hubei Jianghan), and its function is to promote bonding. In this embodiment, the silane coupling agent is specifically a combination of KH792 and KH560, and the mass ratio thereof is 2:1. At this ratio, it can have the best bonding and detachable effects.
[0071] The catalyst is an organic tin compound, and the addition of the catalyst helps to quickly cure. The organic tin compound includes dibutyltin diacetylacetonate, dioctyltin dilaurate, U303 (a reaction product of tetraethyl orthosilicate and di(acetyloxy)dibutyltin), etc. In this embodiment, the catalyst is specifically a tin catalyst U303 (manufacturer Nitto Chemical).
[0072] 2. Preparation method of detachable modified silane sealing adhesive
[0073] The preparation method of the detachable modified silane sealing adhesive provided in this embodiment is divided into four steps, which are as follows:
[0074] 1. According to the optimal formula of the detachable modified silane sealing adhesive in this embodiment, weigh the modified silane polymer, plasticizer, dewatering agent, filler, thixotropic agent, ultraviolet absorber, light stabilizer, dye or pigment, silane coupling agent, and catalyst respectively.
[0075] 2. Add the modified silane polymer, plasticizer, filler, dye or pigment, and thixotropic agent into a double planetary stirring kettle at room temperature, disperse for 0.5 hours under vacuum, then control the temperature to above 100° C. under vacuum, dehydrate for 2-4 hours, and activate the thixotropic agent at the same time;
[0076] 3. Control the temperature at about 43°C, add UV absorber and light stabilizer, and stir for 10-15 minutes under vacuum;
[0077] 4. After cooling to below 43°C, add dehydrating agent, silane coupling agent and tin catalyst in sequence, stir for 10-15 minutes each under vacuum, and after stirring evenly, a removable modified silane sealing adhesive is obtained.
[0078] In the preparation method, the moisture content must be ensured to be less than 1000 ppm, and the temperature must be controlled below 43° C. when adding a dehydrating agent, a silane coupling agent, and a catalyst. The order of materials within the steps can be changed, but the order between the steps cannot be changed.
[0079] The removable modified silane sealing adhesive prepared in this embodiment can quickly cure with moisture at room temperature to form an elastomeric sealing adhesive, which can achieve good mechanical properties and is stable in storage. It can hang a weight of at least 10 kg and has good adhesion to various common home improvement substrates. It can quickly form a strong removable modified silane sealing adhesive. At the same time, it can meet the requirement of being "removable" at room temperature without the aid of any other additives, solvents, degumming agents, etc., and the peel strength is close to 0 N / mm, which is suitable for use as a sealing adhesive that requires repeated cycles or repair and removal.
[0080] Example 2 Different formulations of a removable modified silane sealing adhesive
[0081] 1. Removable modified silane sealing adhesives made from different formulas
[0082] In this embodiment, different formulas are used to prepare removable modified silane sealing adhesives. The preparation method is basically the same as that in Example 1 of the present invention, and the main difference lies in the different raw material formulas. The specific raw material formulas are shown in Table 1 (in mass percentage).
[0083] Table 1, Example formula ratio
[0084]
[0085]
[0086] 2. Performance Testing
[0087] The following performance tests were performed on the removable modified silane sealing adhesives prepared in Examples 1 to 3 of the present invention and the removable modified silane sealing adhesives prepared in Comparative Examples 1 to 4:
[0088] (1) Adhesion test: scrape a 100*15mm*2mm adhesive strip on the substrate. Place it in a constant temperature room (23°C, 50% relative humidity) for 168 hours, cut the adhesive strip with a knife, and disassemble it 180 degrees. Record the adhesive strip's adhesion and appearance. If the cohesive failure is greater than 20%, it is recorded as unqualified (the cohesive failure greater than 20% is a peel test, which qualitatively determines whether it can be peeled or disassembled);
[0089] (2) Mechanical properties of colloid: After the rubber strip was placed in a constant temperature room (23°C, 50% relative humidity) for 168 hours, the tensile strength and elongation at break were tested according to GB / T 528. The Shore A hardness was tested according to GB / T 531.1. After the Al+Al shear specimen was placed in a constant temperature room (23°C, 50% relative humidity) for 168 hours, the tensile shear strength was tested according to GB / T 7124; the peel strength was tested according to GB / T 2791 test standard.
[0090] (3) Test of the number of “removable” times: different removable modified silane sealing adhesives were applied to the substrate board respectively, and after being placed in a constant temperature room (23°C, 50% relative air humidity) for 168 hours, the adhesives were removed from the substrate board by hand, and the bonding effect and peel strength were measured respectively according to the test standard GB / T 2791; after successful removal, the same adhesive was applied to the substrate board again, placed under the same conditions, and then removed again, and the bonding effect and peel strength were measured again; the above steps were repeated until the adhesive could no longer be bonded to the substrate board, and the complete number of removable times was recorded (the complete number of removable times refers to successful bonding to the substrate board and then successful removal, which is a complete “removable”; the standard for “successful bonding to the substrate board” is: shear strength ≥1.0Mpa, cohesive failure 100% CF).
[0091] The test results of the above performance test are shown in Table 2 below:
[0092] Table 2. Performance test results of removable modified silane sealing adhesives prepared with different formulas
[0093]
[0094] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the amount of sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability"; ⑤The "removable" means "whether a complete disassembly can be performed".
[0095] As can be seen from Table 2, compared with the comparative example, Examples 1 to 3 all successfully achieve "detachability", and at the same time, they are well bonded to the substrate, and the mechanical properties are also excellent. The hardness, tensile strength, and elongation at break all have high strength, which can meet the need to hang a weight of 10 kg. This shows that the detachable modified silane sealing adhesive prepared in Examples 1 to 3 of the present invention is suitable for use as a sealing material for home decoration, construction, and handmade DIY; and when the best formula in Preferred Example 3 (Example 1) is used, the detachable modified silane sealing adhesive obtained has the smallest peel strength, achieves the best "detachable" performance, and can be completely disassembled at least 8 times, significantly saving materials and costs.
[0096] Example 3 Effect of “filler” on the preparation of removable modified silane sealing adhesive
[0097] 1. Selection of “filler”
[0098] In this embodiment, the method provided in Example 1 is used to prepare a removable modified silane sealing adhesive, wherein when adding fillers (the information of the fillers is described in Table 3), the addition is performed in the manner described in Table 7, thereby preparing different removable modified silane sealing adhesives. The performance of each group of removable modified silane sealing adhesives is tested according to the performance testing method in Example 2, and the specific results are shown in Table 3 (in this embodiment, only the components of the fillers are changed, and other components and proportions not mentioned are as described in the optimal formula in Example 1).
[0099] Table 3, information of different fillers
[0100] Light calcium carbonate Heavy calcium carbonate Fumed Silica Talc 1 Talc 2 Aluminum hydroxide Particle size 0.06 micron 5 microns 0.015 micron 0.5 micron 15 microns 1.5 micron
[0101] Table 4. Effects of removable modified silane sealing adhesives made from different modified silane polymers
[0102]
[0103] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability".
[0104] As can be seen from Table 4, when no filler is added, the bonding strength of the prepared detachable modified silane sealing adhesive is extremely poor, and it is also not detachable, which does not meet the requirements of the present invention; and when the filler is added, the bonding strength is significantly improved. This may be because the addition of the reinforcing filler fills the gaps between the polymer chains, thereby improving the bonding strength.
[0105] At the same time, the use of different fillers also has different effects on the bonding performance of the prepared removable modified silane sealing adhesive. The experimental results show that compared with other combinations of fillers, adding a mixture of "heavy calcium carbonate + talcum powder 2 + aluminum hydroxide" as a filler can effectively improve the bonding effect of the prepared removable modified silane sealing adhesive, and at the same time, under the premise of ensuring the bonding effect, it can also significantly reduce the peel strength; and the particle size of the heavy calcium carbonate is 1um-10um, the particle size of talcum powder is 10um-30um, and the particle size of aluminum hydroxide is 0.5um-5um, so it is preferred to use 5μm heavy calcium carbonate, 15μm talcum powder 2, and 1.5μm aluminum hydroxide; and when the filler is continued to be added on this basis, the bonding performance of the finally prepared removable modified silane sealing adhesive will be significantly reduced, which cannot meet the needs of the present invention. This may be because there are too many fillers of different particle sizes, and the proportion of effective bonding components decreases, resulting in a decrease in bonding effect, durability, and the rubber strip is more likely to crack. Only when the filling ratio of "heavy calcium carbonate + talcum powder 2 + aluminum hydroxide" is in the range of (1-5): (1-5): (50-55), and the total filling amount is less than 60%, can the ideal effect be achieved. Within this range, as the ratio changes, the properties such as bonding strength and peel strength will also change accordingly. When further research and experiments were conducted on different ratios, it was found that when the preferred mass ratio of heavy calcium carbonate, talcum powder, and aluminum hydroxide is (4-5): (4-5): (50-51), it can simultaneously have good high bonding strength and low peel strength performance. After more experimental verification, the best effect was achieved when the filling ratio of heavy calcium carbonate, talcum powder, and aluminum hydroxide was 4.8:4.8:50. This may be because the reinforcing filler can meet the required high bonding strength and low peel strength at the appropriate ratio of 4.8:4.8:50, and the total filling amount is less than 60% to effectively ensure the durability of the product. This specific ratio relationship enables the fillers to work better together. The smaller particle size filler can fill the gaps of the larger particle size filler to form a tight and uniform filling structure, affecting the physical properties of the adhesive. The small particle size filler increases the contact area and filling density, enhances the cohesion, and the large particle size filler builds a skeleton structure to improve the overall stability, thereby achieving ideal bonding and detachable effects.
[0106] Therefore, in this embodiment, the filler "heavy calcium carbonate + talcum powder 2 + aluminum hydroxide" is preferably used to prepare the removable modified silane sealing adhesive. While ensuring that the plasticity and bonding effect are significantly improved, the peel strength can also be minimized, successfully achieving "removability".
[0107] 2. Optimization of the amount of aluminum hydroxide, heavy calcium carbonate and talcum powder added
[0108] In this embodiment, "heavy calcium carbonate + talcum powder 2 + aluminum hydroxide" is preferably used as the filler, and the effects of different added masses of heavy calcium carbonate, talcum powder 2 and aluminum hydroxide on the preparation of removable modified silane sealing adhesive are further investigated. The specific addition method is shown in Table 5.
[0109] Table 5. Effects of removable modified silane sealing adhesives prepared with different addition weights of heavy calcium carbonate, talcum powder 2 and aluminum hydroxide
[0110]
[0111]
[0112] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability".
[0113] As can be seen from Table 5, the different addition masses of heavy calcium carbonate, talcum powder 2 and aluminum hydroxide result in large differences in the performance of the obtained removable modified silane sealing adhesive. When any one of the components is increased or decreased, thereby changing the addition ratio of the three components, the performance of the obtained removable modified silane sealing adhesive will be significantly reduced. Only when the addition ratio of "heavy calcium carbonate + talcum powder 2 + aluminum hydroxide" in the filler is 4.8:4.8:50, the obtained removable modified silane sealing adhesive has the best performance. While ensuring that the plasticity and bonding effect are significantly improved, the peel strength can also reach the minimum, and "removability" is successfully achieved.
[0114] Example 4 Effect of “Combination of Modified Silane Polymer and Plasticizer” on Preparation of Removable Modified Silane Sealing Adhesive
[0115] In this embodiment, the method provided in Example 1 is used to prepare a removable modified silane sealing adhesive, wherein when adding the modified silane polymer and the plasticizer, they are added respectively in the manner described in Table 6, thereby preparing different removable modified silane sealing adhesives, and the performance of each group of removable modified silane sealing adhesives is tested according to the performance testing method in Example 2. The specific results are shown in Table 6 (in this embodiment, only the components of the modified silane polymer or the plasticizer are changed, and the other unmentioned components and proportions are as described in the optimal formula in Example 1, and the modified silane polymer is a base substance and a component that must be added, so the case where no modified silane polymer is added is not considered here).
[0116] Table 6. Effects of removable modified silane sealing adhesives made with different components
[0117]
[0118] Note: ①CF represents cohesive failure, CF greater than 90% represents good bonding, and AF represents bonding failure; ② "Hardness, tensile strength, elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③ Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④ "Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it is difficult to achieve "removability"; ⑤INOVOL C220 is a polyether diol with a molecular weight of 2000, and INOVOL C240 is a polyether diol with a molecular weight of 4000, purchased from Shandong Yinuowei Polyurethane Co., Ltd.
[0119] It can be seen from Table 6 that when different combinations of modified silane polymers and plasticizers are used to prepare removable modified silane sealing adhesives, they have completely different effects on bonding failure, shear strength, hardness, tensile strength, elongation at break, peel strength and whether it is removable.
[0120] Compared with the case of adding modified silane polymer alone, adding modified silane polymer and plasticizer at the same time can more effectively improve the bonding effect and withstand the sealing pressure. At the same time, under the premise of ensuring the bonding effect, the peel strength can be significantly reduced to as low as 0.25N / mm, thereby significantly reducing the difficulty of "removability". This may be because the modified silane polymer and plasticizer are added at the same time, so that the filler is more fully dispersed and the synergistic effect is more obvious. While ensuring the required bonding strength, the modified silane polymer and plasticizer plus a certain proportion of fillers increase the modulus of the system and reduce the toughness of the system, thereby showing a reduced peel strength.
[0121] At the same time, different combinations of modified silane polymers and plasticizers have completely different effects on improving the bonding effect and peel strength of the removable modified silane sealing adhesive. After many experiments, it was found that the removable modified silane sealing adhesive made by the combination of modified silane polymer SAX750 and plasticizer DINP can significantly improve the bonding effect while achieving the lowest peel strength, successfully achieving "removability", and the peel strength is only 0.25N / mm. When the combination of modified silane polymer SAX750+SAX400 and plasticizer DINP is used, the bonding effect is better, but the peel strength is improved to 0.85N / mm. This may be because the coordination between different types of resins leads to better wettability of the system, improves a certain peel strength, and makes the system more difficult to peel.
[0122] Therefore, in this embodiment, it is still preferred to use a combination of modified silane polymer SAX750 and plasticizer DINP to prepare a detachable modified silane sealing adhesive, which can significantly improve the bonding effect while minimizing the peel strength, thus successfully achieving "detachability".
[0123] Example 5 Effect of "Modified Silane Polymer" on the Preparation of Removable Modified Silane Sealing Adhesive
[0124] In this embodiment, the method provided in Example 1 is used to prepare a removable modified silane sealing adhesive, wherein when adding the modified silane polymer, the addition is performed in the manner described in Table 7, thereby preparing different removable modified silane sealing adhesives, and the performance of each group of removable modified silane sealing adhesives is tested according to the performance testing method in Example 2. The specific results are shown in Table 7 (in this embodiment, only the components of the modified silane polymer are changed, and other components and proportions not mentioned are as described in the optimal formula in Example 1).
[0125] Table 7. Effects of removable modified silane sealing adhesives made from different modified silane polymers
[0126]
[0127] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability".
[0128] As can be seen from Table 7, since the modified silane polymer is the basic substance of the detachable modified silane sealing adhesive of the present invention and is a component that must be added, when the modified silane polymer is not added, the bonding effect and the tolerable sealing pressure of the obtained detachable modified silane sealing adhesive are extremely poor, which is completely unable to meet the use requirement of hanging a 10kg weight and does not meet the requirements of the present invention. Therefore, in this embodiment, the case where no modified silane polymer is added is not described in detail.
[0129] At the same time, the use of different modified silane polymers also has different effects on the bonding effect and peel strength of the prepared detachable modified silane sealing adhesive. The experimental results show that compared with other modified silane polymers, adding SAX750 as a modified silane polymer can effectively improve the bonding effect and the tolerable sealing pressure of the prepared detachable modified silane sealing adhesive, and at the same time, under the premise of ensuring the bonding effect, the peel strength can also be significantly reduced; and when two modified silane polymers are used in combination, the final detachable modified silane sealing adhesive has a good bonding effect, but the final peel strength is also significantly improved, which significantly increases the difficulty of realizing "detachability" of the present invention. This may be because the coordination between different types of resins leads to better wettability of the system, improves a certain peel strength, and makes the system more difficult to peel.
[0130] Therefore, in this embodiment, it is still preferred to use modified silane polymer SAX750 to prepare a detachable modified silane sealing adhesive, which can significantly improve the bonding effect while minimizing the peel strength, thus successfully achieving "detachability".
[0131] Example 6 Effect of "Plasticizer" on Preparation of Removable Modified Silane Sealing Adhesive
[0132] In this embodiment, the method provided in Example 1 is used to prepare a removable modified silane sealing adhesive, wherein when adding the plasticizer, it is added in the manner described in Table 8, thereby preparing different removable modified silane sealing adhesives, and the performance of each group of removable modified silane sealing adhesives is tested according to the performance testing method in Example 2. The specific results are shown in Table 8 (in this embodiment, only the component of the plasticizer is changed, and other components and proportions not mentioned are as described in the optimal formula in Example 1).
[0133] Table 8. Effects of removable modified silane sealing adhesives made with different plasticizers
[0134]
[0135] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability".
[0136] As can be seen from Table 8, when no plasticizer is added, the plasticity of the prepared detachable modified silane sealing adhesive is extremely poor, and the peel strength is significantly improved, which makes it significantly more difficult to achieve "detachability", and does not meet the requirements of the present invention; when the plasticizer is added, the plasticity of the prepared detachable modified silane sealing adhesive can be significantly improved, and the peel strength is also significantly reduced, thereby significantly reducing the difficulty of "detachability". This may be because the addition of plasticizer is more conducive to infiltration to achieve good bonding, and is more conducive to full mixing between the components, playing a coordinated role, and achieving peelability.
[0137] At the same time, the use of different plasticizers also has different effects on the plasticity and peel strength of the obtained removable modified silane sealing adhesive. The experimental results show that compared with other plasticizers, adding DINP as a plasticizer can effectively improve the plasticity of the obtained removable modified silane sealing adhesive, and at the same time, under the premise of ensuring the bonding effect, it can also significantly reduce the peel strength; when using a combination of two plasticizers, the final removable modified silane sealing adhesive has good plasticity, but the final bonding effect and the tolerable sealing pressure are significantly reduced, and it cannot meet the requirement of the present invention to be able to hang at least 10kg of weight. This may be because the coordination between different plasticizers reduces the coordination between fillers, and the final peelable requirements cannot be achieved.
[0138] Therefore, in this embodiment, it is still preferred to use DINP as the plasticizer to prepare the removable modified silane sealing adhesive, which can significantly improve the plasticity and bonding effect while minimizing the peel strength, thus successfully achieving "removability".
[0139] Example 7 Effect of "Silane Coupling Agent" on Preparation of Removable Modified Silane Sealing Adhesive
[0140] 1. Selection of "Silane Coupling Agent"
[0141] In this embodiment, the method provided in Example 1 is used to prepare a removable modified silane sealing adhesive, wherein when adding the silane coupling agent, it is added in the manner described in Table 9, thereby preparing different removable modified silane sealing adhesives, and the performance of each group of removable modified silane sealing adhesives is tested according to the performance testing method in Example 2. The specific results are shown in Table 9 (in this embodiment, only the components of the silane coupling agent are changed, and other components and proportions not mentioned are as described in the optimal formula in Example 1).
[0142] Table 9. Effects of removable modified silane sealing adhesives prepared with different silane coupling agents
[0143]
[0144] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability".
[0145] As can be seen from Table 9, when no silane coupling agent is added, the bonding effect and stability of the obtained detachable modified silane sealing adhesive are extremely poor, and it is completely unable to meet the use requirements of hanging 10kg weights, and does not meet the requirements of the present invention; and when the silane coupling agent is added, the bonding performance of the obtained detachable modified silane sealing adhesive can be significantly improved, meeting the use requirements of the present invention, and at the same time, under the premise of ensuring the bonding effect, the peel strength can be significantly reduced, thereby significantly reducing the difficulty of "detachable". This may be because the silane coupling agent promotes the improvement of the bonding ability of the system, so the bonding strength is significantly improved, and the bonding effect is significantly improved, but the synergistic effect between the silane coupling agent and the powder enables the peel strength to be reduced, thereby achieving detachability.
[0146] At the same time, the use of different silane coupling agents also has different effects on the bonding effect, stability and peel strength of the prepared removable modified silane sealing adhesive. The experimental results show that compared with other silane coupling agents, adding a mixture of KH792 and KH560 as a silane coupling agent can effectively improve the bonding effect, stability and tolerable sealing pressure of the prepared removable modified silane sealing adhesive. At the same time, while ensuring the bonding effect, it can also significantly reduce the peel strength; and when the silane coupling agent is further added on this basis, the final removable modified silane sealing adhesive has a good bonding effect, but the final peeling performance is significantly reduced. This may be because the synergistic effect between the silane coupling agent and the powder enables the reduction of the peel strength, improves the rigidity, and reduces the flexibility, thereby achieving removability.
[0147] Therefore, in this embodiment, the silane coupling agent "KH792+KH560" is preferably used to prepare a removable modified silane sealing adhesive, which can significantly improve the bonding effect while minimizing the peel strength, thus successfully achieving "removability".
[0148] 2. Optimization of the addition amount of "KH792 and KH560"
[0149] In this embodiment, "KH792 and KH560" are preferably used as silane coupling agents, and the effects of different addition amounts of KH792 and KH560 on the preparation of removable modified silane sealing adhesive are further investigated. The specific addition method is shown in Table 10.
[0150] Table 10 Effects of removable modified silane sealing adhesives prepared with different addition amounts of KH792 and KH560
[0151]
[0152] Note: ①CF stands for cohesive failure, CF greater than 90% stands for good bonding, and AF stands for bonding failure; ②"Hardness, tensile strength, and elongation at break", the size of the three indicators reflects the quality of the bonding effect and the size of the sealing pressure that can be borne, including the weight of the object that can be bonded and hung; ③Shear strength>1Mpa is a use requirement, indicating that at least 10kg of weight can be hung; ④"Removable" means that the smaller the peel force, the better, and the peel strength is close to 0N / mm, which is an indicator for judging removability. When the peel strength is>0.5N / mm, it means that it is difficult to achieve "removability".
[0153] As can be seen from Table 10, the different addition amounts of KH792 and KH560 result in large differences in the performance of the prepared detachable modified silane sealing adhesive. When any one of the components is increased or decreased, thereby changing the addition ratio of the two components, the performance of the prepared detachable modified silane sealing adhesive will be slightly reduced. Therefore, the preferred addition ratio of KH792 and KH560 in the present invention is (1-2): (1-2); and when the addition ratio of "KH792+KH560" in the silane coupling agent is 2:1, the prepared detachable modified silane sealing adhesive has the best performance, while ensuring that the plasticity and bonding effect are significantly improved, the peel strength can also reach the minimum, and "detachability" is successfully achieved.
[0154] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A modified silane sealing adhesive, characterized in that: The invention comprises a filler, a modified silane polymer and a plasticizer. The filler comprises aluminum hydroxide and further comprises heavy calcium carbonate and / or talc.
2. The modified silane sealing adhesive according to claim 1, characterized in that: The filler includes a combination of heavy calcium carbonate, talc and aluminum hydroxide.
3. The modified silane sealing adhesive according to claim 2, characterized in that: In terms of mass ratio, the mass ratio of heavy calcium carbonate, talcum powder and aluminum hydroxide in the filler is (1-7.2): (1-7.2): (47.6-55); wherein the particle size of heavy calcium carbonate is 1 μm-10 μm, the particle size of talcum powder is 10 μm-30 μm, and the particle size of aluminum hydroxide is 0.5 μm-5 μm.
4. The modified silane sealing adhesive according to claim 1, characterized in that: The modified silane polymer includes a combination of one or more of SAX750 and SAX400; the plasticizer includes a combination of one or more of phthalate plasticizers, polyether diol plasticizers, and polyether diol plasticizers, the molecular weight of the polyether diol plasticizer is 1000-3000, and the molecular weight of the polyether diol plasticizer is 3000-5000; the modified silane sealing adhesive is a detachable modified silane sealing adhesive.
5. The modified silane sealing adhesive according to claim 1, characterized in that: Based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive includes 40-60% filler, 15-25% modified silane polymer, 10-20% plasticizer.
6. The modified silane sealing adhesive according to claim 5, characterized in that: Based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive includes 45-55% filler, 18-22% modified silane polymer, 10-15% plasticizer.
7. The modified silane sealing adhesive according to claim 6, characterized in that: It also includes a dewatering agent, a thixotropic agent, an ultraviolet absorber, a light stabilizer, a dye or pigment, a silane coupling agent, and a catalyst; the dewatering agent includes a silane dewatering agent; the thixotropic agent includes a polyamide wax thixotropic agent; the ultraviolet absorber includes a benzotriazole ultraviolet absorber; the light stabilizer includes a hindered amine light stabilizer; the catalyst includes an organic tin compound; the silane coupling agent includes a combination of one or more of an amino silane coupling agent and an epoxy silane coupling agent.
8. The modified silane sealing adhesive according to claim 7, characterized in that: Based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive further comprises 0.5-1.5% dewatering agent, 2.5-5% thixotropic agent, 0.15-0.25% ultraviolet absorber, 0.15-0.25% light stabilizer, 0.5-2% dye or pigment, 0.5-3% silane coupling agent, 0.3-1% catalyst.
9. The modified silane sealing adhesive according to claim 8, characterized in that: Based on the total mass of the modified silane sealing adhesive, the modified silane sealing adhesive also includes 0.8-1.2% dewatering agent, 2.5-4% thixotropic agent, 0.15-0.2% ultraviolet absorber, 0.15-0.2% light stabilizer, 0.5-1% dye or pigment, 1-3% silane coupling agent, and 0.4-0.8% catalyst.
10. The method for preparing the modified silane sealing adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) taking a modified silane polymer, a plasticizer, a filler, a dye or a pigment, and a thixotropic agent, dispersing them, heating them to above 100° C. and dehydrating them for 2-4 hours, and activating the thixotropic agent at the same time; (2) Cooling to below 43°C, adding UV absorber and light stabilizer and stirring; (3) Add dehydrating agent, silane coupling agent and catalyst, stir, and obtain modified silane sealing adhesive after stirring evenly.